Time to assess more than prognosis: advancements and challenges in transcatheter tricuspid valve interventions - Rudolph, Felix; Ivannikova, Maria; Rudolph, Tanja K.; Rudolph, Volker; Gerçek, Muhammed; Friedrichs, Kai P. (Frontiers in Cardiovascular Medicine, 2024)
We provide an overview about the current landscape of transcatheter tricuspid valve interventions (TTVI) and summarize recent findings from trials including TRILUMINATE, TRILUMINATE Pivotal, bRIGHT, TRICLASP, TRISCEND, TRISCEND II, TRICUS, and Cardioband TR EFS. These studies have demonstrated the safety and efficacy of TTVI. Yet, they have failed to show a prognostic benefit over conservative treatment. On the other hand, significant improvements in health status assessments have been observed. Assessment of right ventricular (RV) function prior to tricuspid interventions is crucial, as changes in preload and afterload may lead to RV failure which is associated with a high mortality. Therefore, this review emphasizes the impact of TTVIs on quality of life and explores the influence of RV dysfunction on therapeutic success and prognosis.